Efektifitas pemberian terapi musik terhadap Penurunan tekanan darah pada ibu dengan Hipertensi dalam kehamilan - Widayati, Sari -; -, Misrawati -; Woferst, Rismadefis - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aims of this study is to identify the effectiveness of music therapy for reducing blood pressure of women with hypertension during pregnancy. The method of this research was quasy experiment with non-equivalent control group approach. The research was conducted in Puskesmas Rejosari, Tenayan Raya, and Harapan Raya. The samples were 30 that consist of 15 for treatment group and 15 for control group chosen by purposive sampling technique. Treatment group was given music therapy for 15 minute every session for three days. The instrument was spreadsheet for number of blood pressure (BP) measurement. BP measurement device was stethoscope and needle sphygmomanometer. The analysis used univariate and bivariate analysis. Bivariate analysis used Wilcoxon and Mann Withney test. The result of Wilcoxon test was music therapy reduced BP both of systolic and diastolic (p value = 0,02; p value = 0,02; Î±=0,05). Mann Withney test showed p value = 0,017 for systolic BP and 0,044 for diastolic BP (Î±=0,05). This research found that music is effective for reducing BP of women with hypertension during pregnancy and recommends to nurses to apply this music as non pharmacological therapy for reducing BP. Keyword: blood pressure, diastolic,Â  pregnancy,Â  hypertension, music therapy, systolic